Moderation Effects of Tax Planning on the Effect of Incentives Tax, Financial Distress, and Women Directors on Earnings Management: A Case Study on Registered Transportation and Logistics Sector in Indonesia Stock Exchange in 2020-2021) - Jannah, Lu’lu’ul; Hernawati, Erni (Budapest International Research and Critics University, 2022)
This study examines the moderating effect of tax planning on the impact of tax incentives, financial distress, and women directors on earnings management. The sample of this research is transportation and logistics companies listed on the Indonesia Stock Exchange for the observation year 2020-2021. The number of samples that meet the criteria is 42 samples. The variable used in this study is the dependent variable, namely earnings management; the independent variable is tax incentives, financial distress, and women directors, while the tax planning variable is the moderating variable. The analytical method used in this study follows the pattern of the Structural Equation Modeling (SEM) equation model. The data analysis tool uses STATA (Statistics and Data). The results showed that financial distress affected earnings management. In contrast, other variables did not affect earnings management.